Analisis Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Consumer Goods yang Terdaftar Di BEI Tahun 2017-2019 - Yenny Yenny; Siti Aisyah Nasution (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to examine and analyze the factors that influence the capital structure of consumer goods companies listed on the IDX. The research’s method is using quantitative method. The population is taken from manufacturinng companies engaged in consumer goods listed on the IDX from 2017-2019. The total of  samples in this study were 87 samples : it is 29 companies multiplied by 3 research periods. The research model is multiple linear regression. The results of this study are Profitability, Asset Structure, Company Size, and Sales Growth partially have no and no significant effect on Capital Structure in Consumer Goods companies on the IDX for the 2017-2019. Liquidity partially has a negative and significant effect on the capital structure of the Consumer Goods sector companies on the Indonesia Stock Exchange for the 2017-2019.